THE ROLE OF ORAL SPEECH IN THE DEVELOPMENT OF STUDENTS' ECONOMIC THINKING BASED ON THE INTEGRATIVE APPROACH (Web of Teachers: Inderscience Research, 2024)
The article highlights the relevance of integrated education, research activities of students in English lessons, the essence of competence, topical issues of the formation of research skills of students.